2012
DOI: 10.1038/embor.2012.12
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle control of Wnt/β‐catenin signalling by conductin/axin2 through CDC20

Abstract: Wnt/b-catenin signalling regulates cell proliferation by modulating the cell cycle and is negatively regulated by conductin/axin2/ axil. We show that conductin levels peak at G2/M followed by a rapid decline during return to G1. In line with this, Wnt/b-catenin target genes are low at G2/M and high at G1/S, and b-catenin phosphorylation oscillates during the cell cycle in a conductindependent manner. Conductin is degraded by the anaphasepromoting complex/cyclosome cofactor CDC20. Knockdown of CDC20 blocks Wnt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 27 publications
3
74
0
1
Order By: Relevance
“…The capacity that cells have to produce or allow a higher level of b-catenin-TCF complex during the S-G2 phase might therefore provide a basis for the ligand stimulation during the G2-M phase, as observed previously by Davidson and colleagues (Davidson et al, 2009). The accumulation of cytosolic b-catenin during the S-G2 phase might thus result in the elevation of b-catenin that is phosphorylated at residues S33, S37 and T41 in SW480 colon cancer cells (Hadjihannas et al, 2012). We also noted that the oscillation pattern of the level of nuclear b-catenin and that of the b-catenin-TCF complex were similar, although not identical (Fig.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…The capacity that cells have to produce or allow a higher level of b-catenin-TCF complex during the S-G2 phase might therefore provide a basis for the ligand stimulation during the G2-M phase, as observed previously by Davidson and colleagues (Davidson et al, 2009). The accumulation of cytosolic b-catenin during the S-G2 phase might thus result in the elevation of b-catenin that is phosphorylated at residues S33, S37 and T41 in SW480 colon cancer cells (Hadjihannas et al, 2012). We also noted that the oscillation pattern of the level of nuclear b-catenin and that of the b-catenin-TCF complex were similar, although not identical (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…In 1999, the cytoplasmic level of bcatenin protein was found to increase from the G1 to the S phase, and it was suggested that Wnt-b-catenin signaling might function during the G1/S transition (Orford et al, 1999). CDC20-mediated degradation of the Wnt inhibitor AXIN2 during G1-S has also been observed, further supporting a possible peak of Wnt during this time window (Hadjihannas et al, 2012). However, the level of soluble b-catenin, which is not associated with the cytoskeleton and plasma membrane, in synchronized cells is found at the maximal level in G2-M cells (Olmeda et al, 2003).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…To determine whether increased β-catenin signaling sensitizes cells to DNA damage, we expressed constitutively active β-catenin (S33Y) in U2OS cell. These cells, unlike SW480 cells, do not rely on aberrant WNT signaling for cell growth (Hadjihannas et al, 2012). β-Catenin (S33Y) expression resulted in an increase in the number of DNA lesions compared to the number in mock-transfected cells (Fig.…”
Section: Resultsmentioning
confidence: 99%